Projek Ilmiah Tahap Akhir II Wap Web Search Engine (WapFCSIT) / Shariffah Ann Zarina Syed Ahmad Jamalulil - Shariffah Ann Zarina, Syed Ahmad Jamalulil (2003)
This proposal is focusing on the development of WAP ( Wireless Application Protocol ) Web Search Engine using WML ( Wireless Markup Language ) as the domain programming language. The purpose of WAP is to allow people to create and view web pages on wireless devices such as mobile phones or within handheld computers like the Palm. A WAP search engine system is designed for lower bandwidth and small screen viewing while using the ordinary search engine through a wireless device may not be possible or inconvenient. The objective of this project is to develop a search system to enable the users to navigate or browse on the information about FCSlT ( The Faculty of Computer Science and Information Technology ). In this W AP search system, there are two options m finding the FCSIT information. There are hyperlink option and the search option. Both options are capable in retrieving information based on different topics. The scope ofthis project is to retrieve information about FCSIT such as to check the lecturer's email and the semester schedules. To view the search system in a real WAP environment, a simulator and an online WAP browser will be used. The target audiences will be among the student of FCSlT, the lecturers and other people who need to retrieve data on FCSIT. The Waterfall Model is chosen as the methodology to build up this system. The UP.Simulator and Nokia WAP Toolkit will be used as the tools to develop the WAP search system. From the early phase until the finishing phase, the duration of the system development is planned from 24th June 2002 until 7th February 2003.